2016
DOI: 10.17559/tv-20161020210442
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of abrasive wear of Ni-based self-fluxing alloy coatings by the application of experimental design

Abstract: Original scientific paper In this paper resistance to abrasive wear is studied of the Ni-based self-fluxing alloy coatings deposited by flame spraying with fusion. The "dry sand/rubber wheel" test in accordance with the ASTM G65 norm, specifically B and C procedures is used. The experimental data are statistically processed by using analysis of variance, to investigate the influence of two input variables (type of coating: NiCrBSi, NiBSi; spraying distance: smaller, greater) and their interaction on the output… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Resistance to abrasive wear of flame sprayed and simultaneously fused Ni-based self-fluxing alloy coatings (NiCrBSi and NiBSi) of 1-mm thickness, with the application of dry sand/rubber wheel test, was investigated by Havrlisan et al [10]. By applying full factorial design 2 2 with three replicates, for two standardized variants (100 and 2000 revolutions of wheel), authors obtained the regression models, which showed dependence of volume loss on spraying distance and type of applied coating.…”
Section: Flame Sprayingmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance to abrasive wear of flame sprayed and simultaneously fused Ni-based self-fluxing alloy coatings (NiCrBSi and NiBSi) of 1-mm thickness, with the application of dry sand/rubber wheel test, was investigated by Havrlisan et al [10]. By applying full factorial design 2 2 with three replicates, for two standardized variants (100 and 2000 revolutions of wheel), authors obtained the regression models, which showed dependence of volume loss on spraying distance and type of applied coating.…”
Section: Flame Sprayingmentioning
confidence: 99%
“…The usual ways of subsequent remelting are by flame, laser, and in the furnace. However, in the investigations presented in Reference [7][8][9][10][11], NiCrBSi coatings were obtained by one-step process. In investigation Reference [9], the coatings were deposited by plasma spraying system with modified nozzle for enhancing particle heating with an internal powder injector.…”
Section: Introductionmentioning
confidence: 99%